Proposta de priorização em lista de espera e desenvolvimento de software para gerenciamento de cirurgias eletivas no Hospital Universitário Getúlio Vargas em Manaus-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
BACKGROUND: The occurrence of waiting lists for elective surgical intervention is real in several countries with public health systems with “universal” access. The explanation lies in an increasing elective surgical demand, which exceeds the resolution capacity of these systems. It is essential that patients with high need have priority for surgical treatment. Therefore, prioritization criteria have been discussed and adopted for some years in several countries. However, the waiting list for elective surgeries in Brazil, exception of transplants, is organized in chronological order, without defined prioritization criteria by severity. OBJECTIVES: Propose mechanisms for managing the waiting list for elective surgery at HUGV-EBSERH-UFAM. Establish prioritization criteria according to severity to classify patients on the waiting list for elective surgery in the areas of general surgery and digestive tract surgery; Develop software that makes management of the waiting list and assembly of the surgical map easier. METHOD: The methodology used was Action Research. Surgeons who work in the specialties of general surgery and digestive tract surgery at the HUGV-EBSERH-UFAM participated in the study. Data collection was carried out through a structured interview, where a questionnaire previously prepared by the researchers was applied. The measures that were approved by the simple majority of the participants (>50%) established the authors' suggestion so that they are adopted in said Services. RESULTS: All surgeons agreed on the need to adopt clinical criteria for prioritizing patients. The majority of participants (86.67%) agreed with the division of patients into three priority groups, inspired by the system established by the Australian Institute of Health and Welfare's. The researchers presented the clinical situations most commonly found in general surgery and digestive tract surgery outpatient clinics, and the participants defined in which priority group these patients should be classified. These results were summarized in a table that aims to standardize the procedures of surgeons. Software was developed that will facilitate the management of the waiting list, allow the dynamic ordering of patients by clinical and chronological priority criteria. CONCLUSION: The adoption of well-defined prioritization criteria, uniformly followed by all surgeons in the Service, will reduce the waiting time for surgery for those patients who most need the procedure. The use of the developed software will allow greater transparency in the process of scheduling elective surgeries, will facilitate the consultation of the list, will modernize and streamline surgical patient care at HUGV-EBSERH-UFAM and be extended to other institutions that are collating a method that can help them to overcome this difficulty in their daily lives.
Proposal for priorizing a waiting list and software development for managing elective surgeries at Getúlio Vargas University Hospital in Manaus-AM
Keywords: Software - Desenvolvimento; CIENCIAS DA SAUDE: MEDICINA; Cirurgias eletivas; Lista de espera; Gerenciamento; Software